A theological pastoral perspective to prayer ministry in Nigeria - Favour C. Uroko; Blessing Okponung; Attah Ngozika (Khazanah Theologia, 2023)
This article examines prayer ministry in Nigeria from a theological pastoral perspective. The objectives of this study include (1) to assess prayer ministry in Nigeria; (2) to explore reasons for the boom in prayer ministries in Nigeria; (3) to assess the impact of the activities of prayer ministries in Nigeria. Â Existing literature have not adequately explored prayer ministry from a theological pastoral lens. In Nigeria, prayer ministries could be seen all over the place, with the intent of exploiting unsuspecting Nigerians. Religion has been so commercialised and commoditised to the extent that we now have â€œprayer consultants and contractorsâ€ whose task is to assist spiritually â€œweakâ€ people to fast and pray for divine solutions to their problems. Their trademark is to see scary visions about their victims whom they will ask to go on fasting and intense prayers to ward off the looming danger on their lives or those of their family. If the victim says they do not have the strength for such a spiritual exercise, they will offer to help out for a fee. Oftentimes, the so-called vision is a figment of imagination of these fraudsters masquerading as men of God. This study was adopted content analysis through a phenomenological approach. Findings reveal that several of these prayer houses engaged in prayer merchandising, collecting money and material things from their victims, with the promise of prayer for them to gain spiritual and physical freedom. Also, there are reports of immoral activities such as rape happening there. Thus, Christian religious worship is long longer practiced in truth, and prayer houses no longer a place of righteousness, but a place of economic and material exploitationWith this study, Nigerians are better sensitised on how to prevent themselves from falling victim to religious fraud, and the church is also equipped on how to deal with a menace of this nature. Â The article concluded that a theological pastoral perspective of prayer ministry in Nigeria exposes how prayer houses have derailed and started extorting covertly and overtly from the unsuspecting members. The recommendations are discussed.